We Find Strength in Each Other: The Psychosocial Effect of COVID-19 Pandemic on Malay Trans Women in Malaysia - Fathima Begum Syed Mohideen; Nizam Baharom; Mohamed Fakhri Abu Baharin; Khadijah Hasanah Abang Abdullah; Rafidah Hanim Mokhtar; Zainora Daud (USIM Press, 2024)
Ulum Islamiyyah The Malaysian Journal of Islamic Studies Volume 35 Issue 2 PAGE (50-62)